The Role of Mental Imagery in Constructing Meaning - ghilous, salah (El Omda in Linguistics and Discourse Analysis, 2020)
The enormous development carried out by the cognitive sciences imposed on linguistics the transition from transformational generationalism to cognitive, because language is not abstract as Chow Musky sees it, but is an internal case according to the opinion of Jack Andov, who criticized abstraction and focused in his theory on meaning, where we consider that the conceptual structure is the semantic structure, trying to explain it through three components: language, spirit and environment.It considers that the meaning is that mental image that is in the mind about that thing, its relationship to the external science related to the sensory experience, how to perceive the foundations of interaction with the external world and know the nature of the conceptual organization that arises from physical experience which makes it meaningful.